The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.cell.2005.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Emilin1 Links TGF-β Maturation to Blood Pressure Homeostasis

Abstract: TGF-beta proteins are main regulators of blood vessel development and maintenance. Here, we report an unprecedented link between TGF-beta signaling and arterial hypertension based on the analysis of mice mutant for Emilin1, a cysteine-rich secreted glycoprotein expressed in the vascular tree. Emilin1 knockout animals display increased blood pressure, increased peripheral vascular resistance, and reduced vessel size. Mechanistically, we found that Emilin1 inhibits TGF-beta signaling by binding specifically to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
257
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(267 citation statements)
references
References 21 publications
6
257
3
1
Order By: Relevance
“…Consistently, only furin is coexpressed with TGF-b1 in the developing heart, bones, and fetal liver [57]. Another study also showed that Emilin1 can inhibit TGFb1-induced signaling by preventing its furin-mediated cleavage, which is associated with decreased BP [58]. Taken together, these observations demonstrated that furin is the authentic enzyme responsible for TGF-b maturation, suggesting that the furin-TGF-b1 pathway may be the effective target for prevention and treatment of hypertension.…”
Section: Furin May Regulate Bp By Modulation Of Transforming Growth Fmentioning
confidence: 81%
“…Consistently, only furin is coexpressed with TGF-b1 in the developing heart, bones, and fetal liver [57]. Another study also showed that Emilin1 can inhibit TGFb1-induced signaling by preventing its furin-mediated cleavage, which is associated with decreased BP [58]. Taken together, these observations demonstrated that furin is the authentic enzyme responsible for TGF-b maturation, suggesting that the furin-TGF-b1 pathway may be the effective target for prevention and treatment of hypertension.…”
Section: Furin May Regulate Bp By Modulation Of Transforming Growth Fmentioning
confidence: 81%
“…Similar to eln1/2 mice, emilin12/2 mice have significant high renin-induced hypertension and vessels with smaller diameters and thinner walls (Faury et al, 2003;Zacchigna et al, 2006). The absence of EMILIN-1 increases TGFb signaling and, interestingly, the vascular phenotype can be reversed by inactivating one TGF-b allele (emilin-12/2; tgf-b1/2 mice) (Zacchigna et al, 2006).…”
Section: Elastin Microfibril Interface Located Protein (Emilin)-1mentioning
confidence: 99%
“…1,2 All 4 proteins are expressed in the cardiovascular system, however, with significant differences concerning their fine distribution. 1,3,4 While Emilin-1 is expressed by endocardium and right ventricle myocytes and by cells of the entire blood vessel wall (endothelial cells [ECs], smooth muscle cells [SMCs] and adventitial fibroblasts), the other genes have a more restricted expression pattern: Emilin2 is active in myocardium, whereas Mmrn1 and Mmrn2 are expressed only by ECs in blood vessels and, in addition, in platelets and endocardial cells, respectively.…”
mentioning
confidence: 99%
“…One prominent function of Emilin-1 is the regulation of systemic blood pressure (BP). 4 The protein, through its elastin microfibril interface domain, inhibits transforming growth factor (TGF)-β biosynthesis by blocking the proteolytic cleavage of the proTGF-β precursor into the latency associated peptide/TGF-β complex. The increase in TGF-β signaling induced by Emilin-1 deficiency results in systemic hypertension, accompanied by narrowing of arterial tree and structural alterations of the wall of elastic arteries.…”
mentioning
confidence: 99%